Cognitive Fatigue Facilitates Procedural Sequence Learning - Borragán, Guillermo; Slama, Hichem; Destrebecqz, Arnaud; Peigneux, Philippe (Frontiers in Human Neuroscience, 2016)
Enhanced procedural learning has been evidenced in conditions where cognitive control is diminished, including hypnosis, disruption of prefrontal activity and non-optimal time of the day. Another condition depleting the availability of controlled resources is cognitive fatigue. We tested the hypothesis that cognitive fatigue, eventually leading to diminished cognitive control, facilitates procedural sequence learning. In a two-day experiment, twenty-three young healthy adults were administered a serial reaction time task (SRTT) following the induction of high or low levels of cognitive fatigue, in a counterbalanced order. Cognitive fatigue was induced using the Time load Dual-back (TloadDback) paradigm, a dual working memory task that allows tailoring cognitive load levels to the individual's optimal performance capacity. In line with our hypothesis, reaction times in the SRTT were faster in the high- than in the low-level fatigue condition, and performance improvement showed more of a benefit from the sequential components than from motor. Altogether, our results suggest a paradoxical, facilitating impact of cognitive fatigue on procedural motor sequence learning. We propose that facilitated learning in the high-level fatigue condition stems from a reduction in the cognitive resources devoted to cognitive control processes that normally oppose automatic procedural acquisition mechanisms.